Judge's Considerations in Child Custody Disputes: Maqashid Syariah Perspective Analysis of Decision Number 0145/Pdt.G/2015/PA.Ska - Nimas Ayu Sholehah; Isman; Lukmanul Hakim (al-Afkar, Journal For Islamic Studies, 2024)
This research aims to analyze the judge's decision in considering child custody rights given to the father by referring to the Maqasid Syariah perspective. This research will explore the elements that are taken into consideration by judges, including economic, religious and child welfare aspects. By using a qualitative approach and content analysis, the data collected in this research will be analyzed comprehensively based on the judge's decision when considering child custody from the Maqashid Syariah perspective. The findings of this research conclude that the judge's decision regarding child custody is closely related to the psychological behavior of parents towards children in creating child welfare. This is because parents' psychology will influence the child's future development. The study also recommends effective steps to resolve child custody disputes between parents.